A New Methodology for Studying Intraday Dynamics of Nikkei Index Futures Using Markov Chains - Wang, SY (Institutional Knowledge at Singapore Management University, 1999)
The empirical study of intraday patterns of stock trading volatilities and bid-ask spreads in the literature depends on assumptions of specific price generating process and may therefore not be robust to distributional assumptions. By creating discrete states that conform more naturally to the way prices are actually quoted in the derivatives and assets markets, we employ a new methodology of Markov chains for studying the intraday dynamics of derivative prices. We apply the method to study the intraday behavior of the Nikkei index futures prices, trading volumes, and spreads. We find some interesting results such as higher probabilities of transitions between larger volatilities at the opening and closing times. The volatility at lunch break is strikingly low. Contrary to most of the literature, the Nikkei intraday bid-ask spread does not show a U-shaped pattern. We offer some explanations.